The development of teaching materials oriented to critical thinking skills for chemistry class XI high school - Risma Siahaan; Marham Sitorus; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2021)
This study aims to determine the feasibility of teaching materials oriented critical thinking ability grade XI SMA developed. This research includes research and development with 3D development model (define, design and develop). The teaching materials developed were validated based on aspects of material feasibility, language and media by experts using validation sheets in accordance with BSNP standards and then the validated teachng materials were distributed to two teachers and grade XI students at Sultan Agung Private High School and SMAN 1 Pematangsiantar to find out the response of teachers and students using questionnaires. The results of the study found that expert validation of teaching materials developed has an average score of 4.17 in terms of content feasibility, 4.20 for the aspect of presentation feasibility, 4.33 for the linguistic aspect and 4.19 from the aspect of graphation. While students' response to critical thinking ability-oriented module teaching materials had average scores of 3.80 and 3.82 and teacher responses averaged a score of 4.27, judging by interest indicators, material indicators and language indicators. These results show that the critical thinking ability-oriented teaching materials developed have met valid and good criteria for use.Keywords: Teaching materials, Critical thinking skills, Chemical equilibrium, 3D models